ECONOMIC VALUE ADDED, FINANCIAL RATIO, RETURN SAHAM STUDI PADA PERUSAHAAN PUBLIK CONSUMER GOODS PERIODE 2013-2017 - LAILA ZUHRUFAH, ANIS; SISTA PARAMITA, R.A. (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to determine the factors that influence the returns of shares of public consumer goods companies for the period 2013-2017. The type of this research is causal associative research and used quantitative data. The population in this study were 47 companies with a sample of 24 companies taken using purposive sampling. This study uses financial ratios analyzed using multiple linear regression. Financial ratio used in this research were ROA, Current Ratio, DER, PER and NPM. The result in this study indicate that simultaneously EVA, ROA, Current Ratio, DER, PER, NPM affect stock returns. While EVA has a negative effect on stock returns, ROA has a positive effect on stock returns, Current Ratio, DER, PER, NPM does not affect stock returns. Therefore, if investors want to get high stock returns, investors must consider the EVA and ROA variables in making investment decisions. Keywords: economic value added; financial ratio; stock returns.